A general route for the mass production of graphene-enhanced carbon composites toward practical pouch lithium-ion capacitors. Issue 28 (7th July 2021) - An, Yabin; Liu, Tengyu; Li, Chen; Zhang, Xiong; Hu, Tao; Sun, Xianzhong; Wang, Kai; Wang, Chengduo; Ma, Yanwei
Abstract : An efficient and straightforward strategy for constructing graphene-enhanced carbon composites which achieve superior performance in LICs is devised, indicating a general route for mass production of high-performance graphene composites. Abstract : As a promising energy storage system, the lithium-ion capacitor (LIC) shows tremendous potential for energy storage devices with high energy density and power density. However, limited by the poor rate performance of the anode and insufficient capacity of the cathode, its performance needs further improvement. Herein, graphene/soft carbon (G/SC) composites and graphene/activated carbon (G/AC) composites are prepared via a fast self-propagating high-temperature synthesis (SHS) process that can combine the advantages of graphene and carbon materials. For the anode, graphene enriches the reaction interface of soft carbon (SC) and ameliorates the electrochemical reaction kinetics. Therefore, G/SC exhibits superior rate capability (200 mA h g −1 at 4 A g −1 ) together with a high specific capacity of 360 mA h g −1 at 0.1 A g −1 . Meanwhile, due to the excellent graphene network, G/AC exhibits a greatly enhanced conductivity of 2941 S m −1 and an excellent capacity retention of 84% at 10 A g −1 . The LIC based on G/SC and G/AC shows a high energy density of 151 W h kg −1 and a high power density of 18.9 kW kg −1 . Moreover, G/SC is synthesized on a large scale and assembled into a large-capacity LIC pouch cell (1170 F or 650 mA h), which shows an excellent energy density of 31.5 W h kg −1 (based on the total mass of the device) and remarkable cycling performance (93.8% capacity retention after 10 000 cycles at 50C). This work provides a general and effective protocol for ultrafast manufacturing of graphene-based carbon materials toward high-performance lithium-ion capacitors.